Oxygen minimum zone biotic baseline transects for paleoceanographic reconstructions in Santa Barbara Basin, CA. (April 2018) - Myhre, Sarah E.; Pak, Dorothy; Borreggine, Marisa; Kennett, James P.; Nicholson, Craig; Hill, Tessa M.; Deutsch, Curtis
Abstract: We describe modern ocean floor biological trends employing exploratory Remotely Operated Vehicle (ROV) Hercules dives in the Santa Barbara Basin, California, USA, through the Nautilus Exploration Program. Using ROV videos, in situ measurements, and sediment cores, we described oxygenation, temperature, biological zonation, and bulk sediment δ 15 N across three 120-meter vertical transects (from 380 to 500 m, m) that cross the depth of the ventilating sill (475 m) and upper OMZ boundary. These observations revealed major changes in the distribution of biota tied largely to changes in dissolved oxygen concentration. Upward increases in oxygen and temperature were coincident with successive disappearance and appearance of megafauna and foraminifera species and overall increases in community diversity. The most significant and abrupt change in seawater measurements, biological communities, sediment textures, and nitrogen isotopes were observed near the depth of the ventilating sill (from 480 to 450 m). Microbial mats were observed up to the depth of 475 m. Dense populations of Alia permodesta were identified at depths where dissolved oxygen ([O2 ]) was <2.4 µM (from 500 to 460 m). This taxon functioned as marking the boundary between the microbially-dominated and the megafauna-dominated communities. Bulk sediment δ 15 N values were elevated at 460 m, however the mechanism of post-depositional enrichment at this water depth is unclear. These observations have allowed for the refinement of paleoecological reconstructions in margin zonation, as well as a comparative baseline for expected future vertical changes in the OMZ. The modern trends, when integrated with the paleoceanographic record, show that continental margin biotic zonations underwent major vertical migration during the last deglaciation. Conspicuously, at 15, 500 years ago, biotic zonations in the upper water column were vertically compressed towards the ocean surface by 35% compared with modern patterns.